Teaching English to Law Students: Interview with Suman Luhach, School of Law, Bennett University, India - RAHAYU, Rahayu; ANAS, Ismail; UKE, Waode Ade Sarasmita; GENISA, Risma A. Azis (Politeknik Negeri Ujung Pandang, 2023)
She received her Ph.D. from BITS Pilani, Pilani Campus, in 2017. Her observations on college students’ endeavors to pen down their ideas led her to choose Scaffolding Writing Skills for Indian College Students as her doctoral research topic. The work has contributed to understanding the importance of learning management systems to maximally impact classroom instruction of writing skills through a learner-centric, collaborative approach. After being awarded the institutional fellowship in 2011, She taught courses like Technical Communication, Technical Report Writing, and Effective Public Speaking at BITS Pilani to UG and PG students. Before this, She did M. Phil. in English Literature from MGS University, Bikaner, in 2009 and wrote a dissertation on the works of V S Naipaul from a Postcolonial perspective. She qualified for UGC NET (English - Language and Literature) in 2012. While doing a short-term course with RELO, US Embassy, in 2012, She was awarded Outstanding Achievement in Exploring Web 2.0: Tools for classroom teaching and professional development. During her Master (in English Literature), She received Prof. SBL Rawat Memorial Trust Award for achieving the second rank at the University level. She also wrote a dissertation on comparative analysis of G B Shaw’s Caesar and Cleopatra and William Shakespeare’s Antony and Cleopatra in MA. Her research areas are Teaching of Writing Skills in Language Classrooms at Tertiary Level, Online Collaborative Language Learning, literary theories, and Contemporary Drama. She has also served as the co-convenor of Departmental seminars in the Department of Humanities and Social Sciences, BITS Pilani in 2013-14. She was a member of the editorial committee of BITS CAN- a biannual BITS Pilani magazine, and the organizing committee for the International Conference Interfacing Language, Culture and Technology.